Categorizing learners’ needs in English for occupational purposes (EOP): a proposed taxonomy - Amr Selim Wannas; Inas Hussein Hassan (Insights into Language, Culture and Communication)
Teaching English for Specific purposes (ESP) necessitates exerting tremendous efforts and carrying out tasks prior to the implementation of such courses. These tasks involve identifying learners’ needs and developing teaching material with specific discourse. The fact that learners are individuals with unique requirements should be considered, and here is where learning needs come into play. In addition to the learning environment, learning needs should take into account elements like motivation, strategies and skills. The aim of this study is to propose a categorization of learners’ needs during the implementation of ESP courses in professional contexts. To this end, the researchers employed a sequential exploratory research design hypothesizing  and constructing a taxonomy that included four different dimensions of learners’ needs: language, cognitive, psychological and environmental. This was operationalized through an observation process conducted at a Cardiac Care Centre in Aswan, south of Egypt during EOP courses for nurses. To measure learners’ perceptions towards the proposed taxonomy, a questionnaire was disseminated to cardiac care nurses. Preliminary findings have revealed that the responses of the participants (n=94) were positive towards the proposed taxonomy of EOP learners’ needs. Based on the findings of the study, it is recommended that ESP instructors take into consideration cognitive, psychological and environmental needs alongside the language needs of learners prior to and during the implementation of ESP courses.